Community financing of education : issues and policy implications in less developed countries - Bray, Mark, 1952-; Lillis, Kevin (Comparative and international education series, 1988)
This volume discusses the issues relating to community support for education, a topic which has come increasingly to the fore in recent years, especially in the Third World. The book is divided into four main areas: Firstly, an initial explanation of the conceptual framework of the book is given. Secondly, the issues surrounding community financing of education are explored, including community bodies engaged in fund-raising, generating resources, school fees, geographic and social inequalities and central guidance and control. The third section discusses case studies from seven countries, and finally the policy implications of this study are assessed.